Foot care in epidermolysis bullosa: evidence‐based guideline. (1st March 2020) - Khan, M.T.; O'Sullivan, M.; Faitli, B.; Mellerio, J.E.; Fawkes, R.; Wood, M.; Hubbard, L.D.; Harris, A.G.; Iacobaccio, L.; Vlahovic, T.; James, L.; Brains, L.; et al.
Summary: This guideline was designed to provide service providers and users with an evidence‐based set of current best practice guidelines for people and their families and carers, living with epidermolysis bullosa (EB). A systematic literature review relating to the podiatric care of patients with EB was undertaken. Search terms were used, for which the most recent articles relating to podiatric treatment were identified from as early as 1979 to the present day, across seven electronic search engines: MEDLINE, Wiley Online Library, Google Scholar, Athens, ResearchGate, Net and PubFacts.com. The Scottish Intercollegiate Guidelines Network (SIGN) methodology was used. The first guideline draft was analysed and discussed by clinical experts, methodologists and patients and their representatives at four panel meetings. The resulting document went through an external review process by a panel of experts, other healthcare professionals, patient representatives and lay reviewers. The final document will be piloted in three different centres in the U.K. and Australia. Following an EB community international survey the outcomes indicated six main areas that the community indicated as a priority to foot management. These include blistering and wound management, exploring the most suitable footwear and hosiery for EB, management of dystrophic nails, hyperkeratosis (callus), maintaining mobility and fusion of toes (pseudosyndactyly). The evidence here is limited but several interventions currently practised by podiatrists show positive outcomes.